2020
DOI: 10.3390/ijerph17165889
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Understanding COVID-19 Risks and Coping Behaviors among the Elderly Population

Abstract: It is known that the elderly population has weak immune functioning and is a susceptible and high-risk group with respect to the current coronavirus disease 2019 (COVID-19) epidemic. In this study, to understand the influencing factors of COVID-19-related risks and coping behaviors of elderly individuals with respect to COVID-19 and to provide a basis for taking corresponding protective measures, a questionnaire survey was applied to an elderly population. One-way analysis of variance (ANOVA) and linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 8 publications
7
73
2
7
Order By: Relevance
“… 29 A study conducted in China also reported that being female and young age is significantly correlated with COVID-19 preventive measures. 17 Urban residences increase the odds of adherence with COVID-19 preventive measures by ten-fold. A similar result was reported in a study conducted in northwest Ethiopia where rural residence increases the odds of poor COVID-19 practice by three-fold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 A study conducted in China also reported that being female and young age is significantly correlated with COVID-19 preventive measures. 17 Urban residences increase the odds of adherence with COVID-19 preventive measures by ten-fold. A similar result was reported in a study conducted in northwest Ethiopia where rural residence increases the odds of poor COVID-19 practice by three-fold.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was reported in a study conducted in northwest Ethiopia where rural residence increases the odds of poor COVID-19 practice by three-fold. 17 Likewise, a study conducted in China demonstrated that residents who live in cities strongly adhered to the covid-19 protective measures. 17 This may be due to lack of sufficient and accurate information, level of understanding, absence/shortage of media coverage, negligence, low socio-economic status, and low literacy level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 outbreak has seriously affected people’s safety and national security. It is essential to prioritize national strategies to take prevention and control as important tasks, defuse major risks, and enhance the ability to prevent and control public health events as an important part of the national governance system and governance capacity [ 31 ]. It is never too late to take full advantage of this experience for pandemic prevention and major risk control in the field of health.…”
Section: Implications For Improving Public Health System Emergencymentioning
confidence: 99%
“…The COVID-19 pandemic, which is characterized by fast transmission and high infectivity, hit Wuhan, China, in December 2019 [1][2][3]. It spread quickly throughout China and beyond [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%